Practical Aspects of Declarative Languages 17th International Symposium, PADL 2015, Portland, OR, USA, June 18-19, 2015. Proceedings - Pontelli, Enrico.; Pontelli, Enrico.; Son, Tran Cao.; Son, Tran Cao. (Programming and Software Engineering, 2015)
This book constitutes the refereed proceedings of the 17th International Symposium on Practical Aspects of Declarative Languages, PADL 2015, held in Portland, OR, USA, in June 2015. The 10 revised papers presented were carefully reviewed and selected from numerous submissions. The papers cover all forms of declarative concepts, including, functional, logic, constraints, etc.